Artifact-facilitated communication in agile user-centered design - Garcia , Andrei (2018)
The integration of Agile and User-Centered Design methods is a fundamental condition to improve the quality of software products. However, one of the main problems faced to establish this integration on a daily basis is how to facilitate communication among the invariably distinct involved practitioners. Therefore, the purpose of this research is to identify and understand the artifacts involved in the development processes that could facilitate communication between developers and designers in the context of Agile User-Centered Design. This qualitative research is composed of three studies. The first study is a systematic mapping aiming to identify the artifacts used to facilitate communication in an AUCD approach. The second study is also a systematic mapping targeting to present how online ethnography studies have been performed in the Computer Science area. By applying the netnography method, the third study is an online ethnography, which provisions the understanding of how artifacts are used to facilitate communication between designer and developer and when they are used. Through the combination of these three studies, the findings from this research pointed out five themes: (1) Effective teams work together, (2) Designer should play three major roles, (3) Main Artifacts Facilitating Communication, (4) Artifact-Facilitated Communication, and (5) Artifact-Supported Collaboration. The themes interpretation and delineation show the usage of artifacts to facilitates teams’ communication. The findings of this research contribute to Software Engineering and Human-Computer Interaction by providing a broad overview of the artifacts used for communication on AUCD, as well as the software development events that they are used. In addition, the findings demonstrate how Computer Science discipline have been applying online ethnography methods. Finally, they highlight how the artifact-facilitated communication occurs in the industry through a perspective from practitioners that participate in online communities.